Evaluation of Bonus Packs Offered with Price Discounts: The Moderating Effect of Product Type and Price Consciousness - Moon-Yong Kim; Cheong Lee (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Of all the simultaneous offering of multiple promotions found in the marketplace, the current research focuses on offers containing both a bonus pack and a price discount (i.e., BP + PD offers). This research first examines whether consumer evaluations of BP and PD offers differ depending on the product type (vice vs. virtue) and consumers’ price consciousness. Specifically, it is hypothesized that for vice (vs. virtue) products, a BP with a low extra amount also offered with a high PD will be evaluated more positively than a BP with a high extra amount also offered with a low PD (Hypothesis 1). In addition, it is hypothesized that for high (vs. low) price conscious consumers, offers containing the high PD but low extra amount of BP will be more favorably evaluated than offers containing a high extra amount of BP but low PD (Hypothesis 2). Consistent with the hypotheses, the experimental results indicate that product type and consumers’ price consciousness moderate consumer evaluations of BP and PD offers, respectively. The findings imply that manufacturers and retailers can evoke more positive consumer reactions to BP and PD offers, considering different types of product categories and individual differences such as price consciousness.